The professional and personal characteristics of effective psychotherapists: a systematic review - Heinonen, Erkki; Nissen-Lie, Helene A. (Psychotherapy research, 2020)
Objective: Psychotherapists differ notably in the outcomes their patients achieve, and the characteristics that may explain these differences have attracted increasing interest. We systematically review studies on therapist pre-treatment characteristics predicting patient outcomes. Method: Systematic searches on databases for psychotherapy research, clinical psychology, and medical science for the years 2000-2018 identified published research examining therapist characteristics and psychotherapy outcomes. Of 2041 studies, 31 met inclusion criteria. Results: Findings show a few direct effects of therapist intrapersonal variables (e.g., self-relatedness, attachment) and several interaction effects with other constructs (e.g., patient pathology) on outcome. There is little support for the relevance of self-rated social skills. However, more consistent evidence has recently emerged for performance-based measurements of professional interpersonal skills, especially when elicited in challenging situations. Patient outcomes were also predicted by therapists' self-rated professional characteristics, such as their experienced difficulties in practice, coping mechanisms, and attitudes towards therapeutic work, indicating that therapist self-perception also matters, although not always in the direction expected. Conclusions: More effective therapists seem characterized by professionally cultivated interpersonal capacities, which are likely rooted in their personal lives and attachment history. Research guidelines are proposed for moving this field forward (including larger samples, multilevel modeling, and in-depth qualitative work).